Environmental performance assessment in machinery manufacturer - Reis, Juliano Angeli; Sellitto, Miguel Afonso (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The purpose of this article is to assess the environmental performance of a machine manufacturer. The specific objectives of the article were modeling the environmental impact of the object; measure the object after a questionnaire; and interpret the results from the perspective of the operational strategy of the company. Environmental performance is a measure that describes how an anthropogenic organization manages its relationship with the environment. Environmental performance is an inherently multidimensional measure. In the model adopted in this article, the measured dimensions are compliance with legislation, the consumption of materials and energy resources, air emissions, effluents, and solid waste. The environmental performance is measured on a scale ranging from zero to 100%. The assessment was based on environmental performance indicators, in separate constructs, and judged by categorical questionnaire. Its measurement can be used as input for the planning of energy and environmental policies. The outcome of the case was higher than 70%.